2020
DOI: 10.7759/cureus.9894
|View full text |Cite
|
Sign up to set email alerts
|

Perceptions, Practices, and Challenges Regarding Menstrual Hygiene Among Women in Karachi, Pakistan: A Comparison Between General Population and Healthcare Workers

Abstract: Background Menstruation is a natural physiological phenomenon, yet considered a stigmatized subject, particularly in low- and middle-income countries like Pakistan. It is seldom discussed openly, leading to flow of incorrect and incomplete knowledge. The resultant unhealthy practices not only affect the health of the menstruator but can also contribute to considerable psychosocial stress. Menstrual hygiene management (MHM) is an important facet, which is associated with a variety of practices and be… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
13
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 14 publications
(16 citation statements)
references
References 23 publications
3
13
0
Order By: Relevance
“…In contrast, the present study reported a low percentage of the study population who had good knowledge about the menstrual cup (5.8%). This finding is similar to the finding of the study by Arshad Ali et al In this study authors reported that only 11.4% of the general study population knew about the menstrual cup [8] . The present study reported that most of the participants use sanitary napkins (96.7%) during their menstruation cycle for maintenance of menstruation hygiene.…”
Section: Discussionsupporting
confidence: 92%
“…In contrast, the present study reported a low percentage of the study population who had good knowledge about the menstrual cup (5.8%). This finding is similar to the finding of the study by Arshad Ali et al In this study authors reported that only 11.4% of the general study population knew about the menstrual cup [8] . The present study reported that most of the participants use sanitary napkins (96.7%) during their menstruation cycle for maintenance of menstruation hygiene.…”
Section: Discussionsupporting
confidence: 92%
“…Similar findings were provided in a study conducted in St. Louis, Missouri, USA, where over two-fold (64%) of women were unable to afford the necessary menstrual hygiene supplies, during their reproductive cycles 1,4 . A Canadian poll indicated that one-third of menstruators struggled to manage their finances to afford menstrual supplies 9 . Notably, by recording the association between economic status and the ability to acquire menstrual hygiene supplies, the researchers discovered that over two-thirds of low-income women could not afford these essential hygiene items 12 .…”
Section: Resultsmentioning
confidence: 99%
“…Due to the limited dissemination of information, individuals hold myths and preconceived notions that manifest in their hazardous menstruation practices. This not only has medical consequences, such as an increased risk of urinary tract infections (UTIs) and reproductive tract infections (bacterial vaginosis, vaginal scabies, candidiasis), but also contributed to significant emotional stress 9 .…”
Section: Introductionmentioning
confidence: 99%
“…However, menstrual hygiene can be defined as making use of clean, hygienic menstrual material to absorb blood that can be changed in privacy as often as possible; making use of soap and water for washing the body as required and being able to dispose of used menstrual waste properly [5]. In low and middle-income countries such as Nigeria, several misconceptions are linked with menstruation as it is considered as something that should be suffered in silence and 'shrouded in secrecy [6]. Menstruating women and girls are believed to be impure and contaminated and have limited or no access to appropriate toilets and facilities for handwashing [7].…”
Section: Introductionmentioning
confidence: 99%
“…Furthermore, many adults, as well as parents and close relations in Nigeria, are hesitant to openly discuss issues regarding sexual health, reproduction, and menstruation [8]. As a result, it serves as a major challenge to proper Education regarding menstrual hygiene and has blocked the access of adolescent girls to the right kind of information, especially in the rural and tribal communities [6,9].…”
Section: Introductionmentioning
confidence: 99%